Pengembangan Sistem Informasi Pengelolaan Data Siswa Smp Negeri 2 Wewewa Barat Berbasis Web - Aldio Ama Kii; Stefanus D.I.Mau; Dian Fransiska Ledi (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2026)
The development of information technology requires educational institutions to manage data quickly, accurately, and in an integrated manner to support effective administration and decision-making. SMP Negeri 2 Wewewa Barat still uses a semi-manual spreadsheet-based system in managing student data, which has the potential to cause duplication, recording errors, information delays, and the risk of data loss. This study aims to develop a web-based student data management information system that can improve efficiency, accuracy, and data security. The method used is a system development with a Waterfall approach that includes needs analysis, design, implementation, testing, and maintenance. Data were collected through observation, interviews, and documentation. The system was built using PHP and MySQL and designed as a multi-user web application. The results show that the system is able to centrally integrate student, teacher, class, and grade data, simplify the input, search, update, and reporting processes, and increase security through access rights settings. Thus, this system effectively improves school administration performance and supports real-time data management.